1999
DOI: 10.1037/0021-843x.108.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory processes and the course of depression.

Abstract: The authors report a 6-month follow-up study of clinically depressed patients. At baseline, 2 indexes of autobiographical memory functioning were assessed: the presence of spontaneous intrusive memories of stressful life events and performance on the Autobiographical Memory Test (J. M. G. Williams & K. Broadbent, 1986), which measures overgeneral memory. The index of overgeneral memory was associated with greater levels of spontaneous intrusion of stressful memories. Overgeneral memory did not predict outcome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
5
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 36 publications
12
150
5
2
Order By: Relevance
“…About 29% of the first responses were OGMs, which is comparable to Brewin et al (1999), but lower than the percentage reported by Brittlebank et al (1993;54%). Information on the stability of scores is provided in Table 2.…”
Section: Amt Performance and Its Stabilitymentioning
confidence: 50%
“…About 29% of the first responses were OGMs, which is comparable to Brewin et al (1999), but lower than the percentage reported by Brittlebank et al (1993;54%). Information on the stability of scores is provided in Table 2.…”
Section: Amt Performance and Its Stabilitymentioning
confidence: 50%
“…First, prior research has raised concerns regarding the reliability of autobiographical memory and recall of lifetime abuse, especially among individuals with a history of depression (Brewin, Reynolds, & Tata, 1999;Mackinger, Pachinger, Leibetseder, & Fartacek, 2000). Second, the cumulative nature of lifetime assessments can potentially confound the inter-pretation of data from longitudinal studies that include multiple assessments as it can be difficult to determine whether results represent exposure from past versus recent events.…”
Section: Current Studymentioning
confidence: 99%
“…Segundo Kuyken e Dalgleish (1995), nos sujeitos deprimidos existe um enviesamento negativo das memórias autobiográficas que é fundamental para a génese da depressão e sua manutenção, na medida em que reforça o ciclo depressivo. A depressão está assim associada a um enviesamento da memória, em que a quantidade de memórias de situações negativas é superior à de situações positivas (Brewin, Reynolds, & Tata, 1999;Williams, Watts, Macleod, & Mathews, 2000).…”
Section: Memórias Autobiográficas E Depressãounclassified